Hubungan Simtom Insomnia dengan Indeks Massa Tubuh Pelajar MAN 1 Medan - Qodratun Nada Fadilla Azzahara Adlin; Amelia Eka Damayanty; Nanda Sari Nuralita; Fitri Nur Malini Siregar (UMSU, 2025)
Introduction: Insomnia is a condition in which a person has difficulty sleeping, both in terms of quantity and quality. Despite having sufficient sleep duration, individuals with insomnia still cannot achieve adequate sleep. Insomnia can be influenced by body weight, and one of the indicators used to assess a person's nutritional status based on body weight is the Body Mass Index (BMI). Methods: This research is a descriptive analytical study with a cross sectional design, utilizing a sample of 96 participants. The sample is divided into 3 strata, and the data analysis in this research employs univariate and bivariate tests, with the Chi-Square correlation test. Results: The research results indicate that the most common age group was 15 years old, with 37 participants (38.5%), and the majority of respondents were female, totaling 62 individuals (64.6%). The majority of respondents did not experience insomnia, totaling 43 individuals (44.8%), while 30 individuals (31.2%) experienced mild insomnia, 21 individuals (21.9%) experienced moderate insomnia, and 2 individual (2.1%) experienced severe insomnia. Furthermore, the BMI category with the highest prevalence was overweight, with 36 individuals (37.5%), followed by the normal BMI category with 34 individuals (35.4%), the underweight category with 13 individuals (13.5%), and the obese category with 13 individuals (13.5%). Based on the results of the Chi-Square, p = 0.001 (p 0.05) for relationship between insomnia symptoms and BMI. Conclusion: There is a significant relationship between insomnia symptoms and BMI among the students of MAN 1 Medan.